Kajian Motor Tak Serempak Tiga Phasa sebagai Generator Satu Phasa dalam Penerapan Teknologi Efisiensi Energi - Pelpinus Sinay (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
Asynchronous motors, commonly known as induction motors, are widely utilized due to their robustness, reliability, and efficiency in both industrial and household applications. These motors typically operate by converting electrical energy into mechanical energy through the interaction between a rotating magnetic field and the rotor. Under normal operating conditions, the rotor speed is always slightly less than the speed of the magnetic field, which is known as "slip." However, when the slip becomes negative, meaning that the rotor speed exceeds the speed of the rotating magnetic field, the motor begins to function as a generator. This condition occurs when the motor is driven above its synchronous speed by an external mechanical force, causing the rotor to generate electrical power. Using an asynchronous motor as a generator offers several notable advantages. One of the key benefits is its ability to produce a pure sine wave voltage, which is crucial for various applications that require stable and high-quality electrical power. Since these motors do not use brushes, they are free from the problems associated with brush wear and maintenance. Moreover, they do not generate radio frequency interference (RFI), making them suitable for environments sensitive to electromagnetic disturbances. The use of an asynchronous motor as a generator also provides the ability to function as a rotary phase converter. This is especially beneficial in applications where three-phase power is unavailable, but the load requires it. To facilitate this process, a capacitive voltage is required to induce excitation in the rotor. The capacitive current is supplied by an additional capacitor, which is installed in parallel with the motor output. This capacitor helps maintain the necessary phase shift and enables the motor to generate the required three-phase power.